Junie B., first grader : shipwrecked - Park, Barbara; Brunkus, Denise (New York : Random House, 2004)
Junie B.'s first grade class is putting on a Columbus Day play, but the production hits a snag when the students start passing around a flu virus, and bossy May keeps trying to run the show.
"A Stepping Stone Book."
School Library Journal, September 2004.
Book Links (A.L.A.), July 2005.
3.3.
K-3.
560L
Keywords: Jones, Junie B. (Fictitious character) -- Juvenile fiction; Sick -- Juvenile fiction; Theater -- Juvenile fiction; Schools -- Juvenile fiction; Columbus Day -- Juvenile fiction; Diaries -- Juvenile fiction; Jones, Junie B. (Fictitious character) -- Fiction; Sick -- Fiction; Theater -- Fiction; Schools -- Fiction; Columbus Day -- Fiction; Diaries -- Fiction; Jones, Junie B. (Fictional character) -- Fiction; School stories